2019
DOI: 10.1084/jem.20182363
|View full text |Cite
|
Sign up to set email alerts
|

Yeats4 drives ILC lineage commitment via activation of Lmo4 transcription

Abstract: Innate lymphoid cells (ILCs) play critical roles in defending infections and maintaining mucosal homeostasis. All ILCs arise from common lymphoid progenitors (CLPs) in bone marrow. However, how CLPs stratify and differentiate into ILC lineages remains elusive. Here, we showed that Yeats4 is highly expressed in ILCs and their progenitors. Yeats4 conditional KO in the hematopoietic system causes decreased numbers of ILCs and impairs their effector functions. Moreover, Yeats4 regulates α4β7+ CLP differentiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…of the pro-oncogenic protein LMO4: Yeats4 recruits the Dot1l-RNA Pol II complex to the LMO4 promoter in innate lymphoid cells [48]. Our CHIP-seq and CHIP-qPCR data showed a similar pattern in breast cancer cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…of the pro-oncogenic protein LMO4: Yeats4 recruits the Dot1l-RNA Pol II complex to the LMO4 promoter in innate lymphoid cells [48]. Our CHIP-seq and CHIP-qPCR data showed a similar pattern in breast cancer cells.…”
Section: Discussionsupporting
confidence: 57%
“…LMO4, a LIM-only transcriptional regulator, was reported to induce breast cancer invasion and predict poor outcomes [ 46 , 47 ]. Benyu Liu et al reported the mechanism underlying the activation of the pro-oncogenic protein LMO4: Yeats4 recruits the Dot1l–RNA Pol II complex to the LMO4 promoter in innate lymphoid cells [ 48 ]. Our CHIP-seq and CHIP-qPCR data showed a similar pattern in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our flow cytometry results, there is a clear developmental progression of CD34 + cells to more specified progenitors, which correspond with an increase in T-lineage transcription factors. A small cluster of less differentiated cells was present and marked by the expression of LMO4 , likely representing group 2 innate lymphoid cells (ILC2) 24 .…”
Section: Resultsmentioning
confidence: 99%
“…2B) (34). Rora, Icos, Thy1, and Lmo4 are highly expressed by ILC progenitors (9,(35)(36)(37). ROR and Lmo4 are involved in the ILC lineage commitment (27,35,37).…”
Section: Molecular Features Of Pilcps Versus Silcps For Differentiati...mentioning
confidence: 99%
“…Rora, Icos, Thy1, and Lmo4 are highly expressed by ILC progenitors (9,(35)(36)(37). ROR and Lmo4 are involved in the ILC lineage commitment (27,35,37). Top genes that were down-regulated in sILCPs compared with pILCPs included Bcl2, Actg1, several major histocompatibility complex II molecules (H2afy, H2-Ab1, H2-Q7, H2-Aa, and H2-Eb1), Cd74, Egr1, Nfkb1, and Itga4, among others (Fig.…”
Section: Molecular Features Of Pilcps Versus Silcps For Differentiati...mentioning
confidence: 99%